2019
DOI: 10.4103/ajns.ajns_132_18
|View full text |Cite
|
Sign up to set email alerts
|

Giant lumbar dumbbell extradural schwannoma in a child

Abstract: Completely giant lumbar extradural spinal Schwannomas are a rare subgroup of spinal nerve sheath tumors in the pediatric age group. Single stage, single approach, complete, and safe surgical removal while preserving the spinal stability is the mainstay of treatment of giant lumbar extradural Schwannomas. In the present case, we report a case of a 9-year-old male child studying in 2 nd standard presented with pain in both thighs and legs for 3 months. Magnetic resonance imaging lumbosacra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In a case report and literature review study published in 2021, it was reported that there were 6 cases of giant extradural schwannomas in the pediatric age group without accompanying bromatosis [7][8][9][10][11][12]. No new case report has been published from 2021 to the present.…”
Section: Discussionmentioning
confidence: 99%
“…In a case report and literature review study published in 2021, it was reported that there were 6 cases of giant extradural schwannomas in the pediatric age group without accompanying bromatosis [7][8][9][10][11][12]. No new case report has been published from 2021 to the present.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the gold standard to diagnose especially in spinal tumors [ 24 ]. In MRI, we can determine details of the tumor and surrounding the structures and neural elements [ 25 ]. It showed Iso- or Hypo-intense on T1 weighted and hyperintense on T2 weighted images [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, X-Ray and Computed Tomography (CT) scans are used to evaluate bone windows i.e. details of bone erosion or destruction that can develop into spinal instability [ 25 ]. In this case, there were no apparent abnormalities as well in the thorax X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…In recent reports, MISS techniques have been successfully used in the resection of extradural spinal schwannomas with less soft-tissue destruction, blood loss, and length of hospitalization (►Table 2). 6,9,[17][18][19][20][21][22][23][24][25] The classification according to standardized systems is not often documented and a comparative analysis is difficult to be done as surgical technique could change significantly according to the tumor location and the intra-/extraspinal involvement. It seems from previous studies that open and MISS techniques are comparable in efficacy and safety, and MISS approaches may obviate the need for spinal instrumentation (►Table 2).…”
Section: Discussionmentioning
confidence: 99%